Performance Evaluation of Vertically Oriented Compound Parabolic Concentrating Solar Collector Integrated with Heliostat Field - Sandrasagar, Suresh (IRC, 2020)
Although there are number of studies to investigate the performance of various CPC design but performance of vertically oriented CPC collectors is not evaluated. The lack of research on the operation of vertical CPC collectors integrated with the heliostat field is another motivation for this research. In order to meet this objective, a CPC collector, consisting of 3 evacuated flow through absorbers need to be set up and integrated with three heliostats at the Solar Research site of Universiti Teknologi PETRONAS, Malaysia. The performance of the CPC collector using water as the working fluid determined by recording and analysing various parameters related to heat transfer. This thesis will therefore experimentally determine the thermal performance and feasibility of thermosiphoning of vertically oriented CPC collectors integrated with heliostat field in Malaysia's climate.